KOMPOSISI VEGETASI HABITAT LEBAH MADU (Apis Dorsata) DI KAWASAN HUTAN PENDIDIKAN UNIVERSITAS TADULAKO KECAMATAN BOLANO LAMBUNU KABUPATEN PARIGI MOUTONG - Sudartono, Arief; Korja, I Nengah; Yadi, I Made Ardileks (Universitas Tadulako, 2017)
Habitation is very essential for the survival of organisms because organisms can grow, multiply, feed and interact in their natural habitations. However, habitation destruction will undoubtedly make the organism's survival threatened and extinct. The purpose of this research was to know the vegetation composition of honey bee habitation (Apis dorsata) in Forest Education Area of Tadulako University, Bolano Lambunu District, the Regency of Parigi Moutong. This research used path method by landing initial plot under purposive sampling where honey bee nest found. 4 (four) paths were then made in length of 200 m. Each path consisted of 5 plots with 20 x 20 m, the distance between the plots of each path was 20 m, and the distance between the paths is 60 m. There were eventually 20 plots of observation. Based on the results of the research on the Vegetation Composition of Honey Bee Habitation (Apis dorsata) in Education Forest Area of Tadulako University, Bolano Lambunu District, the Regency of Parigi Moutong, 31 species of plants were found from 24 families in accordance with the tree level, pole, stake, and seedlings. The highest INP value of each level was the tree one with the value of INP of = 29.57%, the pole with INP = 20.83%, the stake with INP of = 26.84%, and the level Seedlings and lower plants with INP of = 22.86%.